Ultrasensitive detection of oncogenic human papillomavirus in oropharyngeal tissue swabs. Issue 1 (December 2017) - Isaac, Andre; Kostiuk, Morris; Zhang, Han; Lindsay, Cameron; Makki, Fawaz; O'Connell, Daniel; Harris, Jeffrey; Cote, David; Seikaly, Hadi; Biron, Vincent
Abstract Background The incidence of oropharyngeal squamous cell carcinoma (OPSCC) caused by oncogenic human papillomavirus (HPV) is rising worldwide. HPV-OPSCC is commonly diagnosed by RT-qPCR of HPV E6 and E7 oncoproteins or by p16 immunohistochemistry (IHC). Droplet digital PCR (ddPCR) has been recently reported as an ultra-sensitive and highly precise method of nucleic acid quantification for biomarker analysis. To validate the use of a minimally invasive assay for detection of oncogenic HPV based on oropharyngeal swabs using ddPCR. Secondary objectives were to compare the accuracy of ddPCR swabs to fresh tissue p16 IHC and RT-qPCR, and to compare the cost of ddPCR with p16 IHC. Methods We prospectively included patients with p16+ oral cavity/oropharyngeal cancer (OC/OPSCC), and two control groups: p16− OC/OPSCC patients, and healthy controls undergoing tonsillectomy. All underwent an oropharyngeal swab with ddPCR for quantitative detection of E6 and E7 mRNA. Surgical specimens had p16 IHC performed. Agreement between ddPCR and p16 IHC was determined for patients with p16 positive and negative OC/OPSCC as well as for healthy control patients. The sensitivity and specificity of ddPCR of oropharyngeal swabs were calculated against p16 IHC for OPSCC. Results 122 patients were included: 36 patients with p16+ OPSCC, 16 patients with p16− OPSCC, 4 patients with p16+ OCSCC, 41 patients with p16− OCSCC, and 25 healthy controls. The sensitivity and specificity of ddPCR of oropharyngeal swabs against p16 IHC were 92 and 98% respectively, using 20–50 times less RNA than that required for conventional RT-qPCR. Overall agreement between ddPCR of tissue swabs and p16 of tumor tissue was high at ĸ = 0.826 [0.662-0.989]. Conclusion Oropharyngeal swabs analyzed by ddPCR is a quantitative, rapid, and effective method for minimally invasive oncogenic HPV detection. This assay represents the most sensitive and accurate mode of HPV detection in OPSCC without a tissue biopsy in the available literature.